INTERPRETING THYROID HORMONE LEVELS IN A PATIENT WITH GRAVES’ DISEASE ON ENOXAPARIN - Cheah, Jean Mun; Tan, Pei Sun; Diah, Mohd Idris Bin Mohammad; Menon, Saieehwaran; Ooi, Xin Yi; Wong, Hui Chin; Yong, Sy Liang (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Enoxaparin, a low molecular-weight heparin, can interfere with free T4 measurements by displacing thyroid hormones from their binding proteins, potentially giving rise to misleading results. Diagnosis becomes particularly challenging in Graves' disease when this interference occurs, as fluctuating thyroid function caused by shifting TSH receptor antibodies is rare in this condition. CASE We report a 38-year-old Malay female who was diagnosed with Grave’s disease in May 2024 and treated with carbimazole. Five months later, she was readmitted for dyspnea and hypoxia and diagnosed with a severe pulmonary embolism. Treatment included thrombolysis with alteplase, followed by anticoagulation therapy using enoxaparin. Upon admission, her anti-thyroid therapy was withheld due to subclinical hypothyroidism, as evidenced by a slightly low free T4 (12.8 pmol/L) and elevated TSH (6.65 iU/L). During her prolonged hospital stay, reassessment revealed discordant thyroid hormone levels, with both free T4 and TSH being elevated, coinciding with the development of hypothyroid symptoms. Assay interference was ruled out through thyroid function tests performed in other laboratories. While anti-TSH receptor antibody was positive, anti-thyroid peroxidase antibody was normal. A multidisciplinary discussion between physicians and biochemical pathologists concluded that the discordant thyroid function test results were likely due to enoxaparin-induced interference (falsely elevated free T4) in the context of her underlying hypothyroid state (elevated TSH). Oral levothyroxine was initiated. Subsequently, her pulmonary embolism treatment was switched to oral rivaroxaban, and further thyroid function tests showed normal free T4 and TSH levels, corresponding to a clinically euthyroid state. CONCLUSION This case emphasizes that when managing Graves' disease with low molecular-weight heparin, clinicians should be aware of potential laboratory interference when interpreting discordant thyroid function test results.